POLICY UNCERTAINTY AND ITS IMPACT ON INVESTMENT RISK IN SUSTAINABLE AGRIBUSINESS VENTURES - Muhamad Solekan (Adisam Publisher, 2025)
Policy uncertainty is one of the factors that significantly affects the investment climate in the agribusiness sector, especially in the context of sustainable development. This study aims to explore the relationship between policy uncertainty and investment risk in sustainable agribusiness efforts in Indonesia. Through a literature review method, this study analyzes various scientific sources and policy documents related to regulatory changes, regulatory inconsistencies, and political and economic uncertainty that impact investment decisions in the agribusiness sector. The results of the study indicate that policy uncertainty can increase financial and operational risks for investors, hinder capital flows, and reduce interest in long-term investment in environmentally friendly agribusiness systems. In addition, this uncertainty weakens legal certainty, increases transaction costs, and reduces market efficiency. This study recommends the importance of cross-sector policy harmonization, regulatory transparency, and legal certainty as a foundation for creating a stable agribusiness investment climate that supports sustainable development goals.